Diseño y simulación de un secador de tambor para disminuir el contenido de humedad en residuos de madera y ser aprovechados como bio-combustible - Ibarra Balarezo, Sandro Adrián (2016)
This research project focuses on the study of a rotary drum dryer that reduces the content of moisture in the waste balsa wood (chips) Company Banova Innovations in Balsa, for subsequent entry to the boiler, which supplies steam at two industrial plants, Banova and Plantabal SA, respectively, in different production processes they develop. The research includes specific data based on the needs of the company and the Bremer boiler, as well as information obtained from research about the object of study, as well as the cost of construction which means implementing the machine to dry the chip continuously. In addition to this it exposed the engineering hours used in the project, depending on the design, selection and sizing of the various components of the dryer drum. By implementing the machine is anticipated to maximize the energy efficiency of the boiler, having the use of a biofuel better quality product reuse wood waste leaving the process with features according to the demands of production. This research project is organized as follows: Chapter I, comprised of problematization, the objectives and rationale for the research. Chapter II, consisting of the theoretical basis, information necessary for the project, where the conceptual and referential rationale used in the research is detailed. Chapter III, covers the methods, types of research, techniques and resources that allowed to carry out the analysis of the material to be dried through research. Chapter IV, the results of the research process and discussion by the problem are detailed. Chapter V, conclusions and recommendations set according to the results obtained are set, based on the objectives of the project. Chapter VI, various literature sources, citations and linkography in which the research process is based are detailed. Chapter VII, made up of data that complement the research necessary to carry out the solution of the problem.